2014
DOI: 10.1007/978-3-662-43790-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Virtual Environment for Training Ball Passing Skills in Rugby

Abstract: Abstract. We have designed a configurable virtual environment to train rugby ball passing skills. Seeking to validate the system's ability to correctly aid training, two experiments were performed. Ten participants took part in ball passing activities, which were used to compare the combinations of different user positions relative to the physical screen, the use of stereoscopic presentation and the use of a floor screen to extend the field of view of the virtual scene. Conversely to what was expected, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
2
2
0
1
Order By: Relevance
“…Such an immersive environment has the potential to offer a more realistic experience (enabling more natural displacements and large display of the environment). Similar results were presented also in smaller LSID presented in [Miles et al 2014], where participants did not estimate correctly target distances in a rugby simulator. However, the evaluation was based on a small number of users (three) and the authors considered just the exposure to 1PP.…”
Section: Throwing Performance In the Three Visual Conditionssupporting
confidence: 90%
“…Such an immersive environment has the potential to offer a more realistic experience (enabling more natural displacements and large display of the environment). Similar results were presented also in smaller LSID presented in [Miles et al 2014], where participants did not estimate correctly target distances in a rugby simulator. However, the evaluation was based on a small number of users (three) and the authors considered just the exposure to 1PP.…”
Section: Throwing Performance In the Three Visual Conditionssupporting
confidence: 90%
“…The results we report here are in accordance with previous work, 5 stating that users underestimate egocentric distance in an LSID VE. Similar results were also reported for smaller LSIDs, 6 where participants did not correctly estimate target distances in a rugby simulator. However, that evaluation was based on a small number of users (three), and the authors only considered the 1PP condition.…”
Section: Comparing User Performancesupporting
confidence: 83%
“…Researchers have shown that 1PP is often preferred in navigation tasks, whereas 3PP is more suitable for tasks that need global knowledge. 6 In ball-catching tasks, the same authors showed that 3PP leads to a better evaluation of distance than other displays when using a head-mounted display (HMD). Several questions remain open: How does changing the visual perspective influence the distance perception in LSIDs?…”
Section: Virtual Reality Software and Technologymentioning
confidence: 99%
“…Covaci, Olivier & Multon, 2015a,b), to analyze distance estimation (e.g. Miles et al, 2014) and to investigate different forms of feedback (e.g. Sigrist et al, 2015).…”
Section: Resultsmentioning
confidence: 99%